Efektivitas Efektivitas Macromedia flash dalam Mengembangkan Kosakata Bahasa Inggris pada Anak Usia Dini - Nur Aini; Elise Muryanti (Program Studi PG-PAUD Universitas PGRI Adi Buana Surabaya, 2022)
This study aims to see the effectiveness of Macromedia Flash in developing English vocabulary in children at Bhakti Bunda Koto Tangah Padang Kindergarten. The research sample consisted of 20 children, of which 10 were control class samples and 10 experimental class samples. The method used is quantitative with a quashi experiment approach. Data processing uses the help of SPSS 25.0 for windows. In this study the data collection techniques used were action tests and documentation. The results of the study show that Macromedia Flash can increase English vocabulary in children. Judging from the experimental class that uses Macromedia flash get higher scores than the control class that uses powerpoint tools. In obtaining the influence test, the value of d = 0.9 is classified as moderate, thus Macromedia Flash is significantly effective for increasing English vocabulary in children.